Pembaruan Pendidikan Islam dalam Era Society 5.0 - Daheri, Mirzon (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2023)
Reconstructionism is a flow in educational philosophy that seeks to change old structures and create a modern cultural order. This school also aims to achieve understanding between individuals in order to regulate human life and the environment. Currently, the development of information technology has reached all levels of society, including Islamic Religious Education. In the era of industrial revolution 4.0, there are three important literacies, namely data literacy, human literacy and technological literacy. Learning in the era of revolution 4.0 can use hybrid/blended learning and case-based learning approaches. In fact, in the era of society 5.0, students can be involved in learning together with robots designed to replace the role of educators. Disruption in the world of education, especially in Islamic Religious Education, cannot be avoided. This article explores the reconstruction of Islamic Religious Education in facing the era of society 5.0. In this way, education actors and stakeholders can understand the importance of technology in Islamic education in the era of society 5.0.